Sex differences in the care of the fetus in the mother's womb and the neonate on her lap: Evidence from demographic surveillance and survey data from Bangladesh - Nurul Alam; Md Mahabubur Rahman; Mamun Ibn Bashar; Ali Ahmed; Taslim Ali; M. Moinuddin Haider (Elsevier, 2022)
Valuation of sons over daughters introduces sex-biased health, economic, and socio-demographic inequalities in many societies. This study aims to examine fetus-sex differences in maternity services and sex differences in medical care for terminally ill neonates in Bangladesh, using secondary data from the Matlab Health and Demographic Surveillance System (HDSS), maintained by icddr,b since 1966 along with data from the Bangladesh Maternal Mortality and Health Care Survey (BMMS) 2016. The HDSS follows a well-defined rural population (0.24 million in 2018) to register vital events and migrations and records the use of maternity services for the index birth and medical care-seeking during the terminal illness of each death in verbal autopsy. The BMMS 2016 recorded maternity care and maternal complications for the last live birth of mothers in the same population (weighted n = 27,133; unweighted n = 26,939). Bivariate analyses estimated the use (in %) of maternity services for the index live births and medical services for terminally ill neonates for each socio-demographic variable. Logistic regression models estimated odds ratios (AORs) adjusted for socio-demographic variables and clustering of births to the same mothers. The HDSS registered 49,827 live births and 1,049 neonatal deaths during 2009-2018. We found similar prenatal care-seeking for male and female fetuses but higher facility delivery (AOR = 1.17, 95% CI: 1.12-1.23) and C-sections (AOR = 1.20, 95% CI: 1.15-1.25) for male fetus pregnancies, differences that remain after adjusting for maternal complications. Sex differences persisted in seeking care for terminally ill neonates. Trained provider consultation (AOR = 1.46, CI: 1.00-2.12); hospital admissions (AOR = 1.43, CI: 1.01-2.03); and dying in hospital (AOR = 1.91, CI: 1.31-2.78) were all higher for male neonates. Other variables positively associated with delivery care and medical care-seeking were lower birth order of the child, higher maternal education, and higher household wealth status. Policy and decision-makers need to be aware of gender disparities in maternity care and care of sick neonates and plan remedial actions.